Internalization of Pancasila Values as an Effort to Prevent Corruption in Indonesia - Joko Sriwidodo (University of Udayana, 2023)
The problem of corruption in Indonesia is complicated. Even though, laws and regulations have been made that regulate sanctions for corruption, there are still many corruptors emerged. Various attempts were made to prevent and eradicate corruption, as a result all the efforts were in vain. So, it is necessary to research discusses